2003
DOI: 10.1038/sj.gt.3301961
|View full text |Cite
|
Sign up to set email alerts
|

Titer determination of Ad5 in blood: a cautionary note

Abstract: Recombinant adenoviruses are presently the most efficient in vivo gene transfer system available. Targeting single organs or large tumors by adenoviral vectors requires an intravascular route of application. During the first pass of viral particles through the vascular bed of the target tissue, virus uptake is not quantitative and undefinite amounts of particles leak into circulation. To determine the amount of leaking particles and to calculate organ-specific uptake (in-/outflow ratio), it is necessary to tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
4
18
1
Order By: Relevance
“…First, the amount of adenoviral vectors associated with cells in blood samples shown in Figure 2B was extremely low compared with that in the plasma. Even the cellassociated vectors could be originally in the plasma and then nonspecifically bind to erythrocytes (Cichon et al, 2003) or be co-precipitated with blood cells during the centrifuging process. Second, most tumour cells injected intravenously accumulated in the lung (Figure 3), which was consistent with data in the literature that lung is the primary target of metastatic tumour cells in mice (Lee, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…First, the amount of adenoviral vectors associated with cells in blood samples shown in Figure 2B was extremely low compared with that in the plasma. Even the cellassociated vectors could be originally in the plasma and then nonspecifically bind to erythrocytes (Cichon et al, 2003) or be co-precipitated with blood cells during the centrifuging process. Second, most tumour cells injected intravenously accumulated in the lung (Figure 3), which was consistent with data in the literature that lung is the primary target of metastatic tumour cells in mice (Lee, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma circulation time, toxicity of polymer-coated adenovirus NK Green et al adenovirus binds extensively to human erythrocytes, 19 a phenomenon not seen in mice, raises an important issue for extravasation of adenovirus following intravenous administration in clinical trials. Our studies have shown that over 90% of a therapeutic dose of type 5 adenovirus is sequestered by human erythrocytes under physiological conditions ex vivo, but that pc-virus shows 10-fold decreased binding (Lyons et al, submitted for publication), which may improve bioavailability of the virus following intravenous injection to patients.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of i.v. administered virus is either sequestered on red cells or cleared by macrophages within minutes of injection (4,5). This can be circumvented by depletion of Kupffer cells and coating the virus with hydrophilic polymers like hydroxypropyl methacrylamide (6), but delivery of the virus to the tumor in large amounts remains a major problem.…”
Section: Introductionmentioning
confidence: 99%